Possibilities for Simulating the Smoke Rollback Effect in Underground Mines Using CFD Software - Adjiski, Vancho (GeoScience Engineering, 2014)
The effect of fire generated smoke rollback in underground mines can be dangerous and a potentially fatal threat to all who are endangered by the fire. Three critical stages in the process of smoke rollback are 3D local phenomena that can be analysed by CFD software simulations. With the help of a 3D-CFD analysis we can observe the critical stages of smoke rollback and their reaction to a ventilation network. The CFD provides the opportunity to expand the range of prediction of smoke spread for a wide spectrum of airflows, fire intensities, mine-section inclinations and layouts. The paper deals with the possibilities for simulating the smoke rollback effect in underground mines using the CFD software. For the purposes of this research paper, the PyroSim software from the company Thunderhead Engineering was used to create three different CFD fire scenarios and then observe the critical stages of smoke rollback effects.